POLA MAKAN DAN AKTIVITAS FISIK SAAT WORK FROM HOME (WFH) SEBAGAI DESKRIPTOR RISIKO DIABETES MELLITUS PADA MASA PANDEMI COVID-19 - Sanny Frisca; Dheni Koerniawan (Jurnal Surya Muda, 2022)
The pandemic era made people abide by recommendations to decline the risk of exposure and transmissions of coronavirus, which one was by work from home (WFH). WFH conducted all daily activities at home, increasing the pattern and quantities of eating without being accompanied by appropriate physical activities or exercise. Thus, it might escalate the risk of DM in people who experience WFH. Changes in eating habits can lead to calorie accumulation in the body. Sedentary habits aggravate this condition in people. As a consequence of this condition, the risk of DM increased. This study aimed to describe eating and activity habits while WFH and risk to DM. This study used an analytic survey with the cross-sectional approach to 60 respondents, which was taken purposively. Data was collected by using a questionnaire about Diabetes Risk from American Diabetes Association (ADA). Most of the respondents have less than 40 years old (71.7%), are female (66.67%), have high school education (53.33%), as private employees (83.33%), and exercise for 30 minutes a week (38.3%). The majority of respondents experienced a different diet (78.3%), gained weight (85%), increased eating quantities (88.3%), and appetites enhancement (91.7%). The risk of diabetes screening result showed that 21.67% have a high risk of diabetes. Even though most respondents have a low risk of diabetes, increasing their diet might escalate the risk. So, it is recommended that the community maintain physical activities for at least 30-60 minutes with mild to moderate aerobic and rearrange the diet as body requirements.